The Rwandan and Namibian genocides in selected novels : a comparative analysis of perpetrators and victims in Running the rift, A Sunday at the pool in Kigali, Mama Namibia and The lie of the land - Visser, Danel (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.